In vivo Confocal Microscopy for Corneal and Ocular Surface Pathologies: A Comprehensive Review - Ramirez-Miranda A; Guerrero-Becerril J; Ramirez M; Vera-Duarte GR; Mangwani-Mordani S; Ortiz-Morales G; Navas A; Graue-Hernandez EO; Alio JL (Clinical Ophthalmology, 2025)
Arturo Ramirez-Miranda,1 Jesus Guerrero-Becerril,1 Manuel Ramirez,2 Guillermo Raul Vera-Duarte,1 Simran Mangwani-Mordani,1,3,4 Gustavo Ortiz-Morales,1 Alejandro Navas,1 Enrique O Graue-Hernandez,1 Jorge L Alio5 1Departamento de Córnea y Cirugía Refractiva, Instituto de Oftalmología Fundación Conde de Valenciana IAP, Mexico City, Mexico; 2Departamento de Córnea y Cirugía Refractiva, Asociación para Evitar la Ceguera en México, Hospital Luis Sánchez Bulnes, Universidad Nacional Autónoma de México, Mexico City, Mexico; 3Surgical Services, Department of Ophthalmology, Miami Veterans Affairs Medical Center, Miami, FL, USA; 4Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami, Miami, FL, USA; 5Research and Development Department, VISSUM Miranza, Alicante, SpainCorrespondence: Arturo Ramirez-Miranda, Instituto de Oftalmologia Fundacion Conde de Valenciana IAP, Chimalpopoca 14, Centro, Cuauhtémoc, Ciudad de México, CDMX, CP 06800, Mexico, Email arturorammir@gmail.comBackground: In vivo confocal microscopy (IVCM) is an advanced imaging technique that enables real-time, high-resolution visualization of corneal microstructures. Its clinical applications have expanded significantly, offering valuable insights into the pathophysiology of various ocular surface and corneal disorders. Despite its utility, challenges in standardization, accessibility, and integration into routine practice limit its widespread adoption.Methods: A comprehensive literature review was conducted using PubMed with the keywords “in vivo confocal microscopy”, “corneal diseases”, and “ocular surface”. From 1835 articles retrieved, studies published within the last seven years with clinical relevance were prioritized, yielding 51 articles. Data were synthesized to evaluate IVCM’s diagnostic capabilities, technical advancements, and applications across corneal pathologies, including infectious keratitis, dystrophies, and post-surgical outcomes.Results: IVCM was shown to provide unparalleled visualization of cellular and subcellular corneal structures, enabling early diagnosis and monitoring of conditions such as keratitis caused by Acanthamoeba and fungi, corneal dystrophies, and nerve regeneration following refractive or transplant surgeries. Innovative applications include its use in regenerative therapies, such as adipose-derived stem cell implantation, demonstrating increases in keratocyte density and stromal integrity. However, limitations include operator dependency, high costs, and the need for further technological refinements, such as wide-field imaging and non-contact modalities.Conclusion: IVCM represents a transformative tool in ophthalmology, bridging the gap between clinical evaluation and cellular-level diagnostics. Advances in imaging technologies and the integration of artificial intelligence hold the potential to overcome current limitations, enhancing its diagnostic precision and applicability. Standardization of protocols and expanded access will be pivotal in establishing IVCM as a cornerstone in the management of corneal diseases and ocular surface disorders.Keywords: In vivo confocal microscopy, IVCM, corneal imaging, ocular surface diseases, regenerative medicine, corneal nerves